Holographic Encryption Applications Using Composite Orbital Angular Momentum Beams - Nian Zhang; Baoxing Xiong; Xiang Zhang; Xiao Yuan (Photonics, 2022)
Optical orbital angular momentum (OAM) holography has been developed and implemented as a vital method for optical encryption. However, OAM holography can only be encoded and decoded with an OAM beam, which limits the level of optical encryption. Here, composite OAM beams are introduced using a computer-generated hologram (CGH) for holographic encryption. The target image is encoded with composite helical mode indices, and the OAM holographic image can only be reconstructed under a specific illuminating composite OAM beam. The experimental results are consistent with the theoretical design and numerical simulations, verifying that composite OAM beams can provide a higher security level for optical holographic encryption. The proposed method can be used to enhance anti-counterfeiting applications, secure communication systems, and imaging systems.